Mechanical Characterization and Thermal Insulation Potential of Hybrid Composites for Energy-Efficient Roofing Applications - Arfis Amiruddin; Partaonan Harahap, ST.,M.T UMSU (Universitas Islam Sumatera Utara, 2026)
This study aims to investigate the mechanical properties and thermal insulation potential of hybrid composites reinforced with palm fiber (ijuk) and durian peel fiber for energy-efficient roofing applications. From an electrical engineering perspective, roofing materials play a crucial role in building energy systems, as they influence heat transfer and the operational load of Heating, Ventilation, and Air Conditioning (HVAC) systems.The composites were fabricated using polyester resin with composition variations of 60/20/20, 70/15/15, 80/10/10, and 90/5/5 through the hand lay-up method. An alkali treatment using 1% NaOH was applied to enhance interfacial bonding between the fibers and the matrix. Mechanical testing was conducted using a Universal Testing Machine (UTM) in accordance with ASTM D695 standards. The results indicate that the 60/20/20 composition exhibited the highest compressive strength of 9.444 MPa, along with the most consistent overall performance. Thermal analysis revealed that the developed composites possess lower thermal conductivity compared to conventional roofing materials, enabling a reduction in heat transfer of up to 28%. In the context of building energy systems, this reduction contributes to decreased cooling loads and lowers HVAC electricity consumption by approximately 669.6 kWh per year. These findings suggest that natural fiber-based hybrid composites have strong potential as multifunctional roofing materials that integrate mechanical strength with energy efficiency in electrically driven building systems.